PENGELOLAAN PERTUNJUKAN KESENIAN TRADISIONAL BERBASIS KOMUNITAS SEBAGAI DAYA TARIK WISATA DI DESA LINGGA, KABUPATEN KARO - Hutajulu, Rithaony; Gulo, Hubari; N.B. Sinulingga, Egi; L. Sholikhah, Rahmatika (Penerbit Lafadz Jaya, 2025)
This Community Partnership Service Program aims to encourage Lingga village tourism marketing strategies through managing arts performances. Lingga Village has typical Karo traditional arts activities which are still maintained to this day. Sanggar Nggara Simbelin is an art studio that still maintains this traditional wealth. This activity aims to make art performances an attraction for tourists to Lingga village as well as increasing learning for the younger generation in the practice of managing a performance and increasing experience in practicing traditional Karo music and dance. The specific target of this activity is to strengthen the promotion of the Lingga tourist village and its traditional riches so that it will again attract the attention of foreign and domestic tourists. The method used in this activity is audio-visual ethnography, namely documentation using an ethnographic approach. This method will involve partners in the process of managing traditional arts performances. From this involvement experience, partners will better understand the packaging process of their traditional arts as part of their promotion and dissemination strategy in the era of digital technology. Management of Karo traditional art performances will help the Lingga village community more easily create a tourist attraction for visiting Lingga village.